Experimental Study on the Crushing Strength of Diamond Grains - Yao, Jianlin; Liu, Bin; Li, Yong (International Journal of Mechanical and Electrical Engineering, 2024)
This study investigates the crushing strength of single diamond grains of varying grades and particle sizes using the WDW-100 electronic universal testing machine. The research aims to understand the mechanical properties of diamond particles, which are critical for optimizing the performance of diamond tools in industrial grinding processes. High-grade diamond particles, characterized by their regular polyhedral shapes and minimal impurities, exhibit higher and more stable maximum load forces compared to medium- and low-grade particles. Medium-grade particles show a balance between strength and brittleness, while low-grade particles display significant variability in their structural integrity due to higher impurity levels and defects. The study also reveals that larger diamond particles tend to have lower average maximum load forces, attributed to increased crystal defects and pronounced grain boundary effects. These findings underscore the importance of considering both the grade and particle size of diamond grains in applications requiring high mechanical strength. The insights gained from this research are essential for improving the design and durability of diamond tools, ensuring their efficiency and longevity in industrial applications.